Concepts in engineering - Holtzapple, Mark T. (McGraw-Hill, 2005)
Concepts in Engineering is an abridged version of Holtzapple and Reece's popular Foundations of Engineering text. Concepts in Engineering describes key engineering topics suitable for a short introduction to engineering course. It provides an overview of engineering professionalism and basic tools students will need in their future studies